2000
DOI: 10.1097/00001888-200005000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Information Needs and Information Seeking in Community Medical Education

Abstract: These findings cast light on information needs and seeking in the context of community medical education. Further research is needed to explore variables such as practice size and access to appropriate Web-based information resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 4 publications
1
31
0
Order By: Relevance
“…Table 1 2–35 provides a comparison of the studies selected for this review. The actual date for data collection, the country where the research was undertaken, the research methodology utilized, the doctors’ professional role and the number of active participants in the research are detailed.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 2–35 provides a comparison of the studies selected for this review. The actual date for data collection, the country where the research was undertaken, the research methodology utilized, the doctors’ professional role and the number of active participants in the research are detailed.…”
Section: Methodsmentioning
confidence: 99%
“…13,14 When primary care practitioners included medical students in their work, the number of questions resulting from patient care decreased, pointing to another kind of time constraint. 15 If best evidence is necessary for good care, practitioners' skills in searching for it must be adequate to address the constraints of time. Easy and convenient access and support services are important to success.…”
Section: Introductionmentioning
confidence: 99%
“…A review study by Davies [58] also seeking the clinical information needs of doctors, conducted an analysis on 15 research studies that suggested the top categories of information needs of doctors were treatment, diagnosis, and drug therapy/information. In a study by Cogdill et al [43] investigating the information needs of primary care physician and students, 162 questions indicating information needs were generated with both physicians and medical students. Questions most frequently asked were related to diagnoses and drug therapy.…”
Section: Assessment and Plan As The Most Important Information In Ambmentioning
confidence: 99%
“…Previous research has not explicitly stated that physicians found HPI useful [15,43,58,59]. The HPI may be important to physicians because it includes a summary and background of what the patient is feeling, which can be helpful for diagnosis and treatment.…”
Section: Assessment and Plan As The Most Important Information In Ambmentioning
confidence: 99%